Citizen's Guide to Useful Resources on the Science and Public Policy of Climate Change - Ponkratz, Ben; Stroik, Paul; Sackmann, Matt; Kuqali, Nicholas (My University, 2010)
Global warming has become a hotly debated topic with much discussion occurring worldwide. The US is currently considering passing legislation mandating reductions in carbon emissions possibly coupled with tax policies and/or a cap and trade system. Based on survey results from both UW-Eau Claire students and Chippewa Valley households there is a general consensus that global warming is real, but it is not clear how concerned we should be regarding this issue. In addition, there is significant uncertainty as to which strategies and policies would be most effective in addressing global warming. Moreover, the vast majority of respondents have little or no familiarity with the current political debate in the US. This project provides a one-stop information clearinghouse for the general public in order to increase awareness regarding both the science of global warming as well as policy strategies to mitigate global warming.
Color poster with text, images, and graphs.
Keywords: Environmental policy--Popular works; Climatic changes--Public opinion; Global warming--Public opinion; Posters; Global warming--Popular works; Global warming--Government policy--Popular works